Role of MicroRNA-155 in Triptolide-induced hepatotoxicity via the Nrf2-Dependent pathway. (5th December 2021) - Li, Yao; Guo, Lin; Hou, Zhenyan; Gong, Hui; Yan, Miao; Zhang, Bikui
Abstract: Ethnopharmacological relevance: Triptolide (TP), the main bioactive and toxic ingredient of Tripterygium wilfordii Hook F, causes severe toxicity, particularly for hepatotoxicity. However, the underlying mechanisms for its hepatotoxicity are not entirely clear. Aim of the study: The purpose of the study was to explore the role of miR-155, a microRNA closely related to various liver injuries and a regulator of the nuclear factor erythroid 2-related factor 2 (Nrf2) antioxidant pathway, in TP-induced liver injury in vitro and in vivo . Materials and methods: First, in vitro L02 cells were treated with different concentrations of TP. The protein levels of Nrf2 and its downstream genes Heme oxygenase1 (HO-1) were determined by Western blot. The mRNA expression of miR-155, Nrf2, NAD(P)H: quinone oxidoreductase 1 (NQO1) and HO-1 were measured using qRT-PCR. And we transfected miR-155 inhibitor and miminc before TP treatment to determine the mRNA and/or protein levels of miR-155, Nrf2 and HO-1. Then, we further confirmed the interaction between miR-155 and Nrf2 pathway in TP-induced hepatic injury in BALB/C mice. The degree of liver injury was determined by HE staining and serum biochemical. The mRNA expression of miR-155 was examined with qRT-PCR and Nrf2 and HO-1 gene expression in liver were evaluated by immunohistochemistry and/or Western blot. Results: The results showed that TP significantly induced the expression of miR-155 both in L02 cells and in rodents liver tissue, and the inhibition of miR-155 could mitigate the hepatic damages caused by TP. Further experiments demonstrated that the inhibition of miR-155 reversed the down-regulation of Nrf2 and HO-1 by TP, while the miR-155 mimic enhanced the effects of TP. Animal experiments also showed that the inhibition of miR-155 by miR-155 antagomir reversed the decrease of Nrf2 induced by TP administration. Conclusions: These results indicated that miR-155 played an important role in TP-induced hepatotoxicity by regulating the Nrf2 signaling pathway. Graphical abstract: Image 1